Population Growth Models of Forest Trees for Conservation Management: Case of Teak (Tectona Grandis) Forest in Begal, East Java, Indonesia - Novriana Sumarti; Mharta A. Wardana; Nuning Nuraini (Bogor Agricultural University, Indonesia, 2018)
Based on 2010 FAO report, teak forest and plantation in Indonesia covers 1,269 million hectares or 7 per mill of total area of Indonesia. It can be found dominantly in Central and East Java. PT Perhutani, Indonesia has responsible for management of the government owned forests in the islands of Java and Madura. Based on 2007 data, the teak wood production is 517,627 m3 and the highest percentage, which is 37% of total production, is coming from East Java. In this paper, we develop growth population models using Leslie Matrix and Markov Chain in order to predict the future condition based on the current condition. The models are implemented into data from Teak Forest in Begal, East Java, that covers 2,052.8 hectares and consists of 114 sites. The result from the first model using Leslie Matrix shows that it needs 16 years from year 2011 that the sustainable condition of the forest can be achieved. The result from the implementation of the second model using Markov Chain into the existing data shows that the condition of the teak forest can be classified as quite critical because the good condition part based on its density of the early age group (0 - 4 years) has potential to become the worst condition before its harvest time.